2020
DOI: 10.1177/0309364620948649
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of persons with transfemoral amputation: Comparison of socket prostheses and osseointegrated prostheses

Abstract: Background: Until recently, no study had compared the quality of life of persons with transfemoral amputation treated with osseointegration to socket prosthesis users. Objectives: Comparison of quality of life in two types of prostheses users: a cohort of patients with osseointegration and patients equipped with a socket prosthesis who were group-matched for age, body mass index and mobility grade. Study design: A cross-sectional study that compared Methods: The quality of life of 39 participants (22 in the os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Furthermore, weight-dependent changes of the soft tissue of the stump can lead to an insufficient attachment of the prothesis (Hoffmeister et al, 2017 ; Beck et al, 2019 ); but there are optional methods to attach the prosthetic leg to the tight stump. The treatment of amputations with transcutaneous osseointegrated prosthetic systems (TOPS) has been established throughout the last two decades in Germany, Sweden, the Netherlands, and Australia (Aschoff et al, 2009 , 2010 ; Juhnke and Aschoff, 2015 ; Juhnke et al, 2015 ; Aschoff, 2017a , b ; Pospiech et al, 2020 ). Compared to the most frequently used “socket suspension” method for prosthetic limb attachment, this method offers a variety of new options (Hagberg et al, 2005 ; Aschoff et al, 2009 ; Frossard et al, 2009 ; Van de Meent et al, 2013 ; Hoffmeister et al, 2017 ; Al Muderis et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, weight-dependent changes of the soft tissue of the stump can lead to an insufficient attachment of the prothesis (Hoffmeister et al, 2017 ; Beck et al, 2019 ); but there are optional methods to attach the prosthetic leg to the tight stump. The treatment of amputations with transcutaneous osseointegrated prosthetic systems (TOPS) has been established throughout the last two decades in Germany, Sweden, the Netherlands, and Australia (Aschoff et al, 2009 , 2010 ; Juhnke and Aschoff, 2015 ; Juhnke et al, 2015 ; Aschoff, 2017a , b ; Pospiech et al, 2020 ). Compared to the most frequently used “socket suspension” method for prosthetic limb attachment, this method offers a variety of new options (Hagberg et al, 2005 ; Aschoff et al, 2009 ; Frossard et al, 2009 ; Van de Meent et al, 2013 ; Hoffmeister et al, 2017 ; Al Muderis et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…This point was recently supported by Pospiech et al. (2021), who compared a group of high-mobility TFA bone-anchored prosthesis users (treated with the German ESKA Endo-Exo-system) (n ​= ​22) to a matched SP control group (n ​= ​17) [ 30 ]. Favourable results for the treated patients were found in the Q-TFA problem and global scores, but the prosthetic use and mobility scores did not differ between the groups [ 30 ].…”
Section: Discussionmentioning
confidence: 96%
“…(2021), who compared a group of high-mobility TFA bone-anchored prosthesis users (treated with the German ESKA Endo-Exo-system) (n ​= ​22) to a matched SP control group (n ​= ​17) [ 30 ]. Favourable results for the treated patients were found in the Q-TFA problem and global scores, but the prosthetic use and mobility scores did not differ between the groups [ 30 ]. This outcome emphasizes the importance of careful patient selection, especially in light of the risk for complications accompanying surgical interventions with implants.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that at least 25% of amputees experience painful neuromas (Sehirlioglu et al, 2009;Bowen et al, 2017). Prior to these innovative surgical techniques, over 100 different treatments were unsuccessful in establishing a standard solution for relief of symptoms, with at least 20-30% of cases being refractory to treatment (Poppler et al, 2018).…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…When compared with individuals with socket prostheses, those with an osseointegrated prosthesis experience an increased sensitivity to vibration (Häggström et al, 2013 ; Clemente et al, 2017 ). Furthermore, numerous studies have shown that osseointegration is associated with improved patient reported outcomes, better prosthesis-associated quality of life, and increased mobility (Brånemark et al, 2019 ; Hagberg et al, 2020 ; Pospiech et al, 2020 ).…”
Section: Surgical Techniquesmentioning
confidence: 99%